Our Most Troubling Madness : Case Studies in Schizophrenia across Cultures - Marrow, Jocelyn; Marrow, Jocelyn; Luhrmann, T. M. (Tanya M.), 1959-; Luhrmann, T. M. (Tanya M.), 1959- (Book collections on Project MUSE., 2016)
"Schizophrenia has long puzzled researchers in the fields of psychiatric medicine and anthropology. Why is it that the rates of developing schizophrenia--long the poster child for the biomedical model of psychiatric illness--are low in some countries and not in others? And why do migrants to Western countries find that they are at higher risk for this disease when they arrive? T.M. Luhrmann and Jocelyn Marrow argue it is because the root causes for schizophrenia are not only biological, but also sociocultural. This book gives an intimate, personal account of those living with serious psychotic disorder in the U.S., India, Africa, and Southeast Asia. It introduces the notion that social defeat--the physical or symbolic defeat of one person by another--is a core mechanism in the increased risk for psychotic illness. Furthermore, 'care as usual' as it occurs in the U.S. actually increases the likelihood of social defeat, whereas 'care as usual' in a country like India diminishes it"--Provided by publisher